PARAMETER IDENTIFICATION AND OPTIMAL CONTROL OF HEAT TRANSFER IN COOLING LINE OF HOT STRIP ROLLING MILL (Сучасні Проблеми Металургії, 2020)
The numerical simulation of mechanical properties of hot-rolled products is of major significance for material characterization as well as material development. The basis for this is the knowledge of the material-specific phase transformations and of the initial microstructure originating from the deformation steps before entering into the cooling line. Additionally, the technological conditions on the run-out table (ROT) are essentially for transformation kinetics.In order to simulate these processes, the plant-specific heat transfer coefficient has to be identified. To this end, steel samples with thermocouples inside are transported with defined velocities through the cooling line of the continuous pilot plant at the Institute of Metal Forming in Freiberg. Furthermore, the material and its movement must be taken into account as characteristics of the ROT. Here, the amount and distribution of the cooling medium, the streaming situation in the segments, the nozzle geometry, and the impact pressure of the cooling medium on the surface of the rolled material are the most important influencing parameters.This paper describes the possibilities for determining and simulating the heat transfer in the cooling line under realistic industrial conditions. In addition, it discusses optimal control strategies for the cooling line to achieve a desired temperature and phase distribution on the run-out table. The results contribute to new technology and material developments at the pilot plant, which are also suitable for the transfer to industry.